1998
DOI: 10.1046/j.1365-2559.1998.00328.x
|View full text |Cite
|
Sign up to set email alerts
|

Value of a panel of antibodies to identify the primary origin of adenocarcinomas presenting as bladder carcinoma

Abstract: For the surgical pathologist, a panel of antibodies consisting of CEA, PSA, OC125 and vimentin is helpful to differentiate primary urinary bladder adenocarcinomas from adenocarcinomas originating from prostate and endometrium, less helpful in differentiation with urachal carcinoma, and not helpful in differentiation with colonic, cervical and ovarian carcinoma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
58
0
1

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(61 citation statements)
references
References 28 publications
2
58
0
1
Order By: Relevance
“…Primary adenocarcinoma of the urological region requires differentiation from more common metastatic adenocarcinomas, including direct, lymphatic and hematogenous spread (22,23). The principal primary organs to be considered include the prostate, colon, female genital tract, appendix, stomach and breast (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Primary adenocarcinoma of the urological region requires differentiation from more common metastatic adenocarcinomas, including direct, lymphatic and hematogenous spread (22,23). The principal primary organs to be considered include the prostate, colon, female genital tract, appendix, stomach and breast (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…15,16,21 The typical colonic adenocarcinoma staining profile, CK7 negative and CK20 positive, has been reported in 29% of primary vesical adenocarcinomas. 15 A combination of CK7 and CK20 by itself does not appear to differentiate primary bladder from colonic adenocarcinomas.…”
Section: 1516mentioning
confidence: 99%
“…The most reliable immunohistochemical marker is prostate-specific antigen, which stains approximately 90% of poorly differentiated prostatic adenocarcinomas and is negative in bladder adenocarcinomas. 3,16 CA 125, which stains the tumor cells of endometrial and ovarian malignancies, has been reported to be of use to differentiate endometrial and ovarian carcinoma from primary bladder adenocarcinomas. 16 Vimentin highlights endometrial carcinoma cells as opposed to bladder adenocarcinoma cells.…”
Section: 1516mentioning
confidence: 99%
See 1 more Smart Citation
“…9 Therefore, very few studies of metastatic spread from primary lung cancer to the bladder have been described.…”
Section: Introductionmentioning
confidence: 99%